Mechanical embolectomy for treatment of large vessel acute ischemic stroke in children. (2nd February 2012) - Tatum, James; Farid, Hamed; Cooke, Daniel; Fullerton, Heather; Smith, Wade; Higashida, Randall; Halbach, Van V; Dowd, Christopher
Abstract : Background and purpose: The three largest adult stroke trials investigating mechanical embolectomy retrieval devices in acute stroke (the Merci, Multi Merci and Penumbra Pivotal Stroke Trials) excluded children. There is a need to expand the literature on mechanical embolectomy in large vessel pediatric arterial ischemic stroke. This paper reports the use of two mechanical embolectomy devices cleared by the Federal Drug Administration (FDA) in four consecutive cases. Methods: Our pediatric stroke database from 2002 to the present was reviewed retrospectively. Patients were included if they were diagnosed with an acute large vessel occlusion, were <18 years of age and underwent recanalization with a device cleared by the FDA. Clinical and radiographic results were abstracted from medical record review. The Pediatric National Institutes of Health Stroke Scale (PedNIHSS) score at presentation and at discharge and a pediatric-modified Rankin Scale (Ped-mRS) at approximately 90 days were scored retrospectively based on documented examinations. Results: Four patients aged 4–17 years with a PedNIHSS score at presentation ranging from 2 to 17 points underwent mechanical embolectomy for reperfusion of the basilar artery (n=3), M1 segment of the right middle cerebral artery (n=1) and right internal carotid artery terminus (n=1). Thrombolysis in cerebral infarction (TICI) grade 3 was achieved in four vessels and TICI grade 2A was achieved in one vessel; there was one asymptomatic intraparenchymal hemorrhage. Intra-arterial tissue plasminogen activator was administered in two vessels. The PedNIHSS score at discharge ranged from 0 to 16 points and the Ped-mRS score at approximately 90 days ranged from 0 to 3 with 75% achieving a Ped-mRS score of ≤2. Conclusion: Mechanical embolectomy using the Merci and Penumbra systems may be a feasible therapeutic option in the treatment of large vessel pediatric arterial ischemic stroke.